How Does Nature Connectedness Improve Mental Health in College Students? A Study of Chain Mediating Effects - Chong Ma; Mei Zhao; Yuqing Zhang (Behavioral Sciences)
How does nature connectedness influence college students’ mental health? To further understand the dynamics at play, this present study delves into the chain mediating roles of resilience and meaning in life, from the perspective of the natural environment’s impact on mental health. In April 2024, researchers utilized quantitative research methods to analyze questionnaire data from 703 college students in China, assessing multiple dimensions such as nature connectedness, resilience, meaning in life, and mental health. The results show the following: (1) All pairs of variables showed significant correlations. (2) Resilience is partly mediated by nature connectedness and mental health. (3) Meaning in life is found to have a partial mediating effect, further elucidating this relationship. (4) A chain mediating role is played by resilience and meaning in life in the connection between nature connectedness and mental health. This study expands the research scope of health psychology, has interdisciplinary research significance, and furnishes theoretical support and important guidance, which are essential in improving college students’ mental health.